Leptin Improves Sperm Cryopreservation via Antioxidant Defense - P Fontoura; M Mello; P Gallo-Sá; MC Erthal-Martins; MC Cardoso; C Ramos (JRI, 2017)
Background: Leptin and its receptor are present in spermatozoa; however, the role of leptin in sperm function is still controversial. Our present study aimed at demonstrating the effect of cryopreservation on sperm DNA fragmentation (DNAf) and investigating the possible effects of sperm capacitation techniques and leptin in vitro incubation on frozen-thawed sperm DNAf and oxidative stress. Methods: Samples of 45 normospermic men attending for infertility investigation at Vida Centro de Fertilidade, Rio de Janeiro, Brazil, were frozen and thawed with or without capacitation and leptin incubation prior to freezing. Sperm DNA fragmentation was evaluated by Sperm Chromatin Dispersion Assay before and after cryopreservation and oxidative stress parameters were measured by spectrophotometry with and without leptin incubation. Statistical analysis was performed using paired t test to compare DNAf between groups before and after freeze-thaw cycle, to compare groups before and after capacitation and leptin incubation and oxidative measurements before and after leptin incubation. Statistical significance was considered when p≤0.05. Results: Our results revealed a significant post-thaw rise in sperm DNAf compared with fresh samples (p=0.0003). Sperm DNAf was significantly reduced when sperm capacitation was performed before freezing, when compared to those frozen with no previous capacitation (p=0.01). The addition of leptin to capacitated sperm before freezing reduced DNAf (p<0.0001) and enhanced superoxide dismutase (p=0.001) and glutathione peroxidase (p=0.02) antioxidant enzymes activity. Conclusion: The addition of leptin to capacitated sperm can improve sperm DNA quality following cryopreservation, possibly by inducing the activity of certain antioxidant enzymes.